The experimental and numerical investigation of flow behavior in an additive manufactured setup with PWM control - Ozlu, Kagan Esat; Yurtseven, Ahmet (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
This study investigates the effects of different perforated plates on internal flow behavior and energy losses of a mini centrifugal fan operating within an additively manufactured air duct. The fan was driven by a PWM (pulsewidth modulation) controller to regulate rotational speed, and both experimental and numerical analyses were performed across a PWM duty cycle range from 10 % to 100 %. The objective was to evaluate how cover resistance influences vortex formation, turbulence dissipation, and total pressure drop. Dimensionless Q-criterion (Q*) contours revealed that increasing resistance intensified the vortical regions and enhanced energy dissipation, HRC exhibits 15.5 % higher vortex volume than MRC, while MRC shows 80.1 % higher vortex volume than LRC. Similarly, the dimensionless turbulence dissipation rate (epsilon*) indicated that high-resistance configurations caused the dissipation zones to extend farther downstream behind the tubes. The dimensionless velocity (v*) contours showed that lower resistances led to more uniform flow, while higher resistances produced pronounced jet-like and heterogeneous velocity distributions. Vorticity analysis confirmed stronger rotational structures under increased resistance conditions. Overall, the results demonstrate that, in the additively manufactured setup, increasing cover resistance amplifies turbulence intensity and vortex activity, leading to higher energy losses and greater total pressure drop.
Keywords: 3-D printed; Mini centrifugal fan; CFD; PWM control; Inflow condition; Vortical flow; CENTRIFUGAL FAN; VERIFICATION; PERFORMANCE; DESIGN; BLADE; Thermodynamics; Mechanics